The effect of institutional ownership on firm performance: the case of U.S.-listed shipping companies - Tsouknidis, Dimitris (My University, 2019)
This paper examines the relationship between institutional ownership and firm performance for U.S.-listed shipping companies using quarterly 13F reports of institutional holdings over the period 2002 to 2016. Traditionally, public shipping companies exhibit a large concentration of ownership as specific individuals and families hold large percentages of the total shares outstanding. However, institutional investors also hold a substantial percentage of ownership of U.S.-listed shipping firms, whose effects on firm performance have not been examined previously in the literature. Results reveal a negative relationship between the percentage of institutional ownership and firm performance, which is primarily attributed to non-strategic rather than strategic institutional investors. This result survives a set of panel data estimators which take into account the presence of dynamic endogeneity in the relationship examined.
Keywords: Dynamic endogeneity; Dynamic panel data; Firm performance; Institutional ownership; U.S. listed shipping companies